Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan Corporate Social Responsibility sebagai Variabel Mediasi - ChandraÃ‚Â Dwi Setyawan; Imam Ghozali (Politeknik Ganesha Medan, 2025)
This study examines the relationship between profitability and firm value with corporate social responsibility (CSR) as a mediating variable. Using purposive sampling, 116 mining companies listed on the Indonesia Stock Exchange (IDX) during 2022-2023 were selected as research samples based on the availability of sustainability reports and annual reports. This study employs multiple linear regression analysis to test the relationships among variables and uses the Sobel test to examine the mediating effect of CSR between independent and dependent variables. The results show that profitability has a positive and significant effect on firm value, CSR has a positive and significant effect on firm value, profitability has a positive and significant effect on CSR, and CSR mediates the relationship between profitability and firm value. In conclusion, although CSR plays a positive mediating role in enhancing firm value, companies need to develop a more serious commitment to CSR implementation to increase public trust and send positive signals to stakeholders.